Injuries among wheelchair basketball players: A systematic review - Wulandari, Novita Sri; Perdana, Suryo Saputra; Azizah, Amalia Nur (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Injuries in wheelchair basketball athletes have detrimental physical and psychological impacts on sports performance. There are numerous injuries occurring during wheelchair basketball games, be it during practice, competitions, or post-events.Purpose: This research aims to determine the frequently occurring injuries among wheelchair basketball athletes.Method: A systematic search was conducted across five databases (PubMed, Google Scholar, Science Direct, Web of Science, and Sports Discus). A systematic review was conducted on Cross-Sectional Studies, and the study quality assessment was performed using NIH.Results: From the systematic review of 5 articles, it indicated that the commonly occurring injury rate focused on the sacral area, accounting for 19.3%.Conclusion: Efforts to reduce the risk of injuries in athletes, particularly in the sacral area, can enhance their quality of life and their ability to achieve better outcomes.